WTI crude oil option implied VaR and CVaR: An empirical application - BARONE-ADESI, Giovanni (Institutional Knowledge at Singapore Management University, 2019)
Using option market data we derive naturally forward-looking, non-parametric and model-free risk estimates, three desired characteristics hardly obtainable using historical returns. The option-implied measures are only based on the first derivative of the option price with respect to the strike price, bypassing the difficult task of estimating the tail of the return distribution. We estimate and backtest the 1%, 2.5%, and 5% WTI crude oil futures option-implied value at risk and conditional value at risk for the turbulent years 2011–2016 and for both tails of the distribution. Compared with risk estimations based on the filtered historical simulation methodology, our results show that the option-implied risk metrics are valid alternatives to the statistically based historical models.